PDF Tunable Optical filters Using Etched Polarization Maintaining Fiber Hybrid Sagnac Interferometer - Taher, Raisan; Mansour, tahreer safa'a (Iraqi Journal of Laser, 2022)
: In modern optical communication system, noise rejection multiple access interference (MAI) must be rejected in dense access network (DAN). This paper will study the dual optical band pass and notch filters. They will be extracted with tunable FWHM using 10cm (PMF) with different cladding diameters formed with etching 125μm PMF after immersing it with 40% of hydrofluoric acid (HF). This fiber acts as assessing fiber to perform Sagnac interferometer with splicing regions that placed 12cm (SMF) for performing hybrid Sagnac interferometer that consists of Mach-Zehnder instead of Sagnac loop which is illuminated by using laser source with centroid wavelength of 1546.7nm and FWHM of 286 pm or 9 ns in the time domain. . Firstly, Three PMF with the same lengths but with different etching durations (10, 20 and 30) min. Secondly, each of these PMFs with different etching durations will affected under tunable stressing forces (10, 20, 50 and100) g applying on cross sectional area and two weights of (5, 10, 25 and 50) g putting on both micro splicing area separately. The minimum FWHM of dual optical band pass and notch filters at specific etching time with mechanical forces getting the best values equal to 123pm and 90pm, respectively. The study found that the HSI interferometer can be used efficiently as a narrow notch filter in integrated optical communication systems since it has high sensitivity in the pm range.